Investigasi Pengaruh Luasnya Pengungkapan Sukarela atas Keberadaan Komite Pengawas Manajemen Pada Perusahaan Manufaktur Di Indonesia - Dinalestari Purbawati; Agung Budiatmo (Jurnal Administrasi Bisnis, 2020)
This study investigated the impact the existence from the oversight committee on the extent from voluntary disclosure of manufacturing company in Indonesia. The oversight committee consist of risk management committee and nomination and remuneration committe. The existence from the oversight committee of manufacturing companies who have never been broad mandatory will have an influence on the differences in the voluntary disclosure between the company which one with a company that other. Data was collected used a documentation technique from the annual reports manufacturing companies listed on the Indonesian Stock Exchange period 2015 until 2017. Sampling method used purposive sampling. The number of samples were 81 companies each year. Multiple linear regression analysis is tools used in this model. The final results showed that in parsial the existence from the risk management committee (RMC) had a positive significant effect of the extent from voluntary disclosure. In simultan test showed that oversight committee had a positive significant effect on the extent of voluntary disclosure. Suggestions for further research is to be able to add the use of data collection method as questionnaires and interviews in knowing more information about the existence of an oversight committee.